Sabellian languages (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The documentation of the Sabellian languages consists of about 1000 inscriptions, ranging from only one alphabetic sign to over 3000 words, and dates back to the period between the 8th and the 1st cent. BCE. We also have c. 50 glosses from Greek and Latin sources. The Sabellian languages are typically featured by combining unity and variety with respect to the I.E. languages outside Italy, to special convergences with Latin and long-lasting contacts with the neighboring languages (Greek and Etruscan). Consequently diverse problems are raised about their definition and classification under different points of views as well as with regard to their impact on the history of Latin. Culturally, combination of unity and variety also feature the alphabetic systems in both geographical and evolutionary perspectives.
Keywords: Sabellian languages; Diachronic changes; Alphabetic multiplicity; Language contacts; Impact on Latin